IBM KELOMPOK TANI SAYURAN DI PATTAPANG - Saida, Saida (Lembaga Pengabdian kepada Masyarakat Universitas Muslim Indonesia, 2017)
Veteran farmer groups and is a Veteran Youth vegetable farmer groups residing in the VillagePattapang, District High Muzzle, Gowa, South Sulawesi. Vegetables grown are cabbage, carrots,potatoes, onion leaves, cabbage, tomatoes, and squash. Land is located on land owned by farmerswith a fairly steep slope so prone to erosion. Cultivation of vegetables is done conventionally byutilizing manure and inorganic fertilizer. Soil cultivation is done in the direction of the slope. Wasbased on the observance of watering, weed control, disease and pest control, but there has not beenoptimal production. Some of the problems encountered in the cultivation of vegetables is themagnitude and does not utilize organic materials in situ, where the organic material produced isburned. Implementation activities undertaken by the team Ipteks form of counseling, training,demonstration plots, and outreach. Materials science and technology as the solution of theseproblems is the processing of organic materials into bokhasi, conservation tillage, and cultivationof vegetables, especially potatoes technology. This activity received a positive response frommembers of farmer groups, due to significantly improve productivity and lower production costs.This becomes a strong motivation for participants to apply the knowledge and technology insustainability efforts.